2004
DOI: 10.1051/forest:2004055
|View full text |Cite
|
Sign up to set email alerts
|

A collection of functions to determine annual tree carbon increment via stem-analysis

Abstract: -Stem analysis process is commonly employed in a wide range of applications of forest importance. We developed a program to compute stem increments in terms of volume, biomass and carbon storage. The stem-analysis process involves the felling of the tree, the extraction of a number of cross-sections from the stem and the measuring of ring-width series on each section. The synchronization of ringwidth series provides a number of tree-and stand-related measures including stem growth pattern, diameter at breast h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…This result confirms the study of Bascietto and Scarascia-Mugnozza [7], who found that the major contributor to carbon increment error was the variability of the wood density measures, and not the variation in carbon content. In total, we selected 174 wood density values from the literature.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This result confirms the study of Bascietto and Scarascia-Mugnozza [7], who found that the major contributor to carbon increment error was the variability of the wood density measures, and not the variation in carbon content. In total, we selected 174 wood density values from the literature.…”
Section: Discussionsupporting
confidence: 81%
“…[7,9,18,41]. Conversion factors are used to calculate amounts of dry mass (t DM) from information on the volume (m 3 ), or to convert dry mass (t DM) into carbon stock (t C).…”
Section: Biomass Expansion Factors Slmentioning
confidence: 99%
“…The four crossdated radii, whose dating was checked by standard dendrochronological techniques (Stokes and Smiley, 1996), were averaged to form a mean disk tree-ring series. All mean disk series of a stem, representative of radial growth at different heights along the stem, were used to calculate the annual stem volume increment using the package "tReeglia" (Bascietto and Scarascia Mugnozza, 2004) of the software R (R Development Core Team, 2005). This program interpolates tree heights at different ages using the Carmean algorithm to yield past pseudoannual estimates of tree height.…”
Section: Laboratory and Numerical Analysismentioning
confidence: 99%
“…Time series were averaged into a mean stand chronology and synchrony was checked by means of the Gleichläufigkeit (sign test) (Kaennel and Schweingruber, 1995) and Student's t-test, to test the significance of the Gleichläufigkeit value being greater than 50%. Stem analysis was performed on each stem, using the Treeglia program (Bascietto and Scarascia-Mugnozza, 2004) to obtain stem historical trend of carbon pools, fluxes and lateral surface area. Tree age was measured as the age of the innermost ring of the stump-height cross-section.…”
Section: Appendix B Field and Laboratory Methodsmentioning
confidence: 99%